2022
DOI: 10.7759/cureus.29022
|View full text |Cite
|
Sign up to set email alerts
|

A Giant Retropharyngeal Lipoma: A Case Report and Review of Literature

Abstract: Lipoma is a common benign soft tissue lesion that can virtually develop anywhere in the body. However, the retropharyngeal space is an extremely rare location for lipoma. We report the case of a 48-year-old man who presented with progressive dysphagia of 3 months duration. It was associated with a weight loss of 6 kg. There was no history of cough, regurgitation, or heartburn. He was a heavy smoker, but he denied consuming alcohol. On examination, the patient was noted to have a hoarse voice. Examination of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Between 2000 and 2020, Alnami reported 27 cases of retropharyngeal lipomas [5]. Our review of the literature has found four supplementary cases.…”
Section: Discussionmentioning
confidence: 74%
“…Between 2000 and 2020, Alnami reported 27 cases of retropharyngeal lipomas [5]. Our review of the literature has found four supplementary cases.…”
Section: Discussionmentioning
confidence: 74%